Plan de negocios para la creación de una residencia universitaria dirigida a los estudiantes de la Universidad de las Américas - Cruz Escalante, Marco Antonio (2017)
Quito is characterized by being one of the cities with the highest number of universities in the country, which means that a large number of students from other provinces arrive every semester with the purpose of developing their university career in Quito. It is possible to find in the surroundings of the University of the Americas different options for renting rooms specially directed to students arriving from other cities, however, not all of them have the set of services required by students. For this reason, the business plan presented is focused on the creation of a university residence aimed to students of the University of the Americas. It will be located in the surroundings of the institution and will offer all the services required by students to develop their university studies in an optimal and safe way. The marketing strategy implemented will be based on the positioning of the service through the enhancement of the offered attributes that differentiate it from the rest of the market, and the pricing will be done through the pricing strategy based on value. The initial investment required for the project is USD 37,999. After the financial evaluation, it was concluded that the project is viable, obtaining a positive NPV and an IRR greater than the estimated discount rate.